PRP4 (RNA4) from Saccharomyces cerevisiae: its gene product is associated with the U4/U6 small nuclear ribonucleoprotein particle. - Bjørn, S P (1989)
The PRP4 (RNA4) gene product is involved in nuclear mRNA processing in yeast cells; we have previously cloned the gene by complementation of a temperature-sensitive mutation. Sequence and transcript analyses of the cloned gene predicted the gene product to be a 52-kilodalton protein, which was confirmed with antibodies raised against the PRP4 gene product. These antibodies inhibited precursor mRNA splicing in vitro, demonstrating a direct role of PRP4 in splicing. Immunoprecipitations with the antibodies indicated that the PRP4 protein is associated with the U4/U6 small nuclear ribonucleoprotein particle.